Analisis Hasil Belajar Materi Perbandingan Berdasarkan Ranah Kognitif Revisi Taksonomi Bloom - Apoliano Da Conceicao E Silva; Siprianus S. Garak; Patrisius A. Udil (Universitas Nusa Cendana, 2023)
This study aims to describe learning outcomes in comparative material based on the cognitive realm of Bloom's taxonomy revision and to determine the factors that influence learning outcomes in comparative material based on the cognitive realm of Bloom's taxonomy revision. This type of research is descriptive qualitative which is analyzed using a descriptive technique approach. The sampling technique used is purposive sampling technique. The sample in this study were all seventh grade students of juior high school 5 Sulamu. The subjects in this study were 22 students. The subjects selected in the interview were 6 students who were selected as interview subjects were taken from the results of high, medium, low criteria and 2 criteria were taken each. Data were collected using test, interview and documentation methods. The results showed that the learning outcomes with the level of remembering on the high criteria are in the good and sufficient category, the medium criteria both in the sufficient category, and the low criteria in the sufficient and less categories. The level of understanding on the high criteria and medium criteria are both in the good category, while the two low criteria are in the sufficient and poor categories. The level of applying the high criteria is in the good category, the medium criteria are in the good and sufficient categories, and the low criteria are in the sufficient and less categories. The level of analyzing on the high criteria is in the good and sufficient category, the medium criteria are in the good and poor categories, and the low criteria are both in the less category. The evaluation level on the high criteria is both in the good category, while the two medium criteria and low criteria are in the less category. The level of creation on the high criteria is both in the good category and the sufficient category, while the two medium criteria and low criteria are in the less category. Internal factors that affect student learning outcomes are lack of accuracy, lack of understanding of students, lack of memory, lack of interest in learning mathematics, lack of confidence, while the external factors that influence student learning outcomes are the lack of family attention. Keywords: Learning Outcomes, Cognitive Domain, Revised Bloom's Taxonomy.